2003
DOI: 10.1136/jech.57.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Previous consultation and self reported health status as predictors of future demand for primary care

Abstract: Study objective: There has been little prospective investigation of what predicts general practice consultation. The objective of this study was to investigate the extent to which previous primary care consultation and self reported health status are predictors of future primary care consultation. Design: Population based cohort study in two phases. Firstly, a baseline survey (1995/96) to identify the cohort and to obtain self reported health status using the UK census limiting long term illness (LLI) question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 6 publications
3
17
0
4
Order By: Relevance
“…Some research shows that CAM users, in line with patients of primary care services more generally [5], are more likely to have poorer self-reported health [1,6]. Other studies have shown that the opposite is true, CAM users tend to have better self-reported health [7,8], or that self-reported health has no influence upon CAM use [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some research shows that CAM users, in line with patients of primary care services more generally [5], are more likely to have poorer self-reported health [1,6]. Other studies have shown that the opposite is true, CAM users tend to have better self-reported health [7,8], or that self-reported health has no influence upon CAM use [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fuera de sistemas nacionales de salud, la CVRS ha mostrado, junto a la morbilidad, su capacidad para predecir el consumo de recursos en AP 20 . Dentro de sistemas públicos, una peor percepción de la CVRS se ha mostrado como predictora de un mayor uso de la consulta del médico de familia en determinadas patologías crónicas como la osteomuscular 21 , o la obesidad 22 , pero por sí sola, solo es una débil predictora del sobreuso de recursos 23 .…”
Section: Introductionunclassified
“…To reduce confounding from "healthy user," "indication" or "treatment" biases, we adjusted for many known confounders, including vaccination target groups and cardiovascular risk groups, treatments and general practitioner consultation rate, of which the latter is thought to be related to functional and economic status. 27 Potential confounders such as functional status were not fully accounted for because of unavailability of data, and we did not have data for other triggers, such as stressful life events. Although we observed missing values for variables such as smoking status, systolic blood pressure, BMI and total cholesterol, we used standard imputation procedures to account for these and obtained results similar to those of our complete case analysis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%